Autism spectrum disorder during French COVID‐19 lockdown: The importance of individualized support. (11th July 2022) - Guidotti, Marco; Gateau, Adrien; Claire, Remi; Rabaté, Philippe; Roux, Sylvie; Malvy, Joëlle; Bonnet‐Brilhault, Frédérique
Abstract: Aim: This observational and repeated measures study assesses the impact of the first, most restrictive, COVID‐19 lockdown in France on children with autism spectrum disorder (ASD) and their families. Method: During the first COVID‐19 lockdown, families of ASD children enrolled in the day‐care centre of the child and adolescent psychiatry department of the Tours University Hospital were contacted weekly. A total of 95 parents took part in this study between the 18th of March and the 8th of May 2020. Advice and personalized support materials were provided by professionals involved in children's care. Questions regarding clinical outcomes were addressed to parents, and their assessments were reported on a 5‐point Likert scale. Two time points were considered: the first 3 weeks and the three last weeks of the lockdown period. Results: No difference was highlighted between clinical scores collected at the beginning and at the end of the lockdown. No effect of intellectual disability, accommodation type (house or apartment) or parental status was observed. The reasons for the relatively minor impact of the COVID‐19 lockdown observed in this study are discussed. Conclusions: Individualized and regular support provided by caregivers, familiar with ASD children's clinical specificities, in the context of a trusted relationship with parents may have contributed to the stability of this population. This 'tailor‐made' approach should be promoted, in order to help support families of ASD children in this challenging period.